2016
DOI: 10.2217/epi-2016-0061
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Epigenetic Programming of Adult Germ Cell Death Disease: Polycomb Protein EZH2–miR-101 Pathway

Abstract: miR-101-EZH2 pathway deregulation could represent a novel pathophysiological epigenetic basis for adult germ cell disease with environmental and developmental origins.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 64 publications
0
11
0
Order By: Relevance
“…In the etiology of chronic diseases, including inter-and transgenerational transmission [23], histone modifications and DNA methylation have been shown to play an important role through the setting of specific chromatin marks and their transmission throughout cell division during life. As such, in a model of early exposure to an environmental challenge (endocrine disruptors), we previously showed that diseases in adulthood were related to sustained impaired repressive histone mark, histone H3 trimethyl lysine 27 (H3K27me3), associated with deficiency in enhancer of zeste homolog 2 (EZH2) [22]. In a model of early exposure to dietary challenge, EZH2-mediated H3K27me3 has been highlighted as one epigenetic mechanism underlying nutritional programming of longevity [27].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the etiology of chronic diseases, including inter-and transgenerational transmission [23], histone modifications and DNA methylation have been shown to play an important role through the setting of specific chromatin marks and their transmission throughout cell division during life. As such, in a model of early exposure to an environmental challenge (endocrine disruptors), we previously showed that diseases in adulthood were related to sustained impaired repressive histone mark, histone H3 trimethyl lysine 27 (H3K27me3), associated with deficiency in enhancer of zeste homolog 2 (EZH2) [22]. In a model of early exposure to dietary challenge, EZH2-mediated H3K27me3 has been highlighted as one epigenetic mechanism underlying nutritional programming of longevity [27].…”
Section: Discussionmentioning
confidence: 99%
“…Our data underlined the alterations in EZH2 as a potential epigenetic hallmark in the early origins of adult diseases related to early life challenges. The mechanisms through which EZH2 exert its effects on organ pathogenesis may involve multiple processes [22,28]. While most studies of EZH2 function have been performed in actively cycling cells such as tumoral cells or stem cells, less have been done in adult mammalian cells which cycle slowly, or adult cardiomyocytes which are mostly post-mitotic.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this regard, an important role may be played by a substantial change in the pattern of HPTMs. Exposure to EDCs has been associated with long-term decreased trimethylation levels of histone H3K27, due to an altered expression in testis of the enhancer of zeste homologue 2 (EZH2) [ 204 ]. Depending on BPA exposure duration, change in two different acetylation marks have also been observed: short exposure increases H3K27Ac, whereas long exposure increases H3K9Ac levels [ 205 ].…”
Section: Epigenetic Mechanisms Are Sensitive To Environment and LImentioning
confidence: 99%
“…infertility) driven by early exposure to endocrine disruptors. 132 Not only in utero exposure affects cardiac micro-RNAs in short term, 128 but also in long term. 133 As such, in mice, a maternal obesogenic diet during gestation and lactation induces miR-133a alteration in the offspring heart at 8 weeks of age associated with cardiac hypertrophy.…”
Section: Micro-rnas Regulate Cardiac Development and Functionmentioning
confidence: 99%